A Novel Method for Additive Manufacturing of Complex Shape Curved Parts by Using Variable Height Layers - Matthieu Rauch; Jorge Piedra Dorado; Jean-Yves Hascoet; Guillaume Ruckert (Journal of Machine Engineering)
The Wire Arc Additive Manufacturing process (WAAM) is designed for the manufacture of large metallic parts. It is gaining its space inside the naval, aeronautics and space industries. However, there are key challenges to be solved in order to increase the performance of the WAAM process. Parts with curved shapes are difficult to manufacture with regular parallel layers without support because of an excessive overhang in certain regions. This paper proposes a methodology that solves this issue, by using incrementally angled layers with variable bead height, which eliminates or decreases the overhang between layers. This solution uses an angled rotary positioner (or other method for moving the part in a controlled way) and controls key parameters like the travel speed, the deposition angle, the available bead height difference, etc. The efficiency of the developed proposal is shown with the manufacture of a large curved steel (316L) piece as a use-case.